Determinantes do crescimento econômico das cidades do Estado do Ceará - Gadelha, Fabiano Pinto (2022)
This article analyzes the determinants of the economic growth of the cities of Ceará during the years 2009 to 2015. For this, it uses a theoretical model estimated in Barro (1991), considering as inputs, to measure the impact on economic growth, the variables arranged in four groups: human capital, financial system, business environment and social infrastructure. The results, obtained from the model incorporating the idea of conditional convergence derived from an extended version of the neoclassical growth model, suggest the human capital stock and the number of commercial/industrial establishments as the main determinants of the economic growth of the cities of Ceará. Thus, it is suggested public policies that involve investments that favor the business ambience in cities that lack establishments in the commerce/industry sector, as well as to expand the number of full-time schools at the municipal level (elementary school) as a state level (high school).